2020
DOI: 10.1186/s43163-020-00047-9
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic CT imaging of deep neck infections (DNIs): how does dual injection mode helps in differentiation between types of collections?

Abstract: Background Deep neck infections are showing resurgence in the current era and still pose threatening diagnosis. CT is the gold standard imaging modality; still, the reported low sensitivity and specificity was suggested in view of monophasic injection technique. The purpose of the study was to discuss the diagnostic accuracy of CT with biphasic mode of injection using and a single scanning phase. The first 50–60 cc of IV contrast are injected at a slow rate of 1 cc/s to (tissue impregnation phase). The other 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Regarding the contrast agent, there is currently no consensus on the optimal amount or speed of administration or the delay between administration and imaging. A recent study found high PPV (0.92) for CT with a biphasic mode of contrast infection and a single scan phase [ 50 ]. The biphasic injection consists of a double mode of injection with single scanning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the contrast agent, there is currently no consensus on the optimal amount or speed of administration or the delay between administration and imaging. A recent study found high PPV (0.92) for CT with a biphasic mode of contrast infection and a single scan phase [ 50 ]. The biphasic injection consists of a double mode of injection with single scanning.…”
Section: Discussionmentioning
confidence: 99%
“…The biphasic contrast injection is suggested to allow better delineation of the abscess walls of different maturations and thus enhance differentiation. However, the superiority of this method lacks scientific studies in comparison to conventional single-phase contrast injections [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical picture of deep fascial infections of the head and neck may not correlate with the worsening of the patient's general condition. The standard diagnostic imaging approach involves computed tomography with contrast [ 27 29 ], which allows for precise location and differentiation of inflammatory disease from other pathologies, such as cysts, tumors, and metastatic lymph nodes [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can be demonstrated by the use of a contrast medium, which accumulates in inflamed tissues. Intravenous contrast also provides a clear visualization of bony and soft tissue structures of the head and neck, allows identification of the great neck vessels, and highlights the areas of inflammation, the collections, and the suspected complications [20]. The differential diagnosis between abscess and cellulitis/phlegmon is critical because surgical drainage is indicated only in the former case [21].…”
Section: Discussionmentioning
confidence: 99%